2017
DOI: 10.1186/s13102-017-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and levels of physical activity in people with severe mental illness: a cross-sectional study

Abstract: BackgroundPhysical fitness is a crucial variable in people with severe mental illness as these people could be more independent and improve their job opportunities. The present study compared the physical fitness of physically active and inactive people with severe mental illness.MethodsPhysical fitness was evaluated in sixty-two people with severe mental illness using 11 physical tests that include strength, flexibility, balance and aerobic condition. Significant differences were found between both groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Physically active individuals may exhibit a decreased risk of falls and fractures because of their higher levels of physical fitness [ 11 , 12 ], and sedentary older adults with poor physical fitness must exert greater effort to execute activities necessary for independent living, which increases their risk of falling [ 13 ]. Therefore, physical fitness assessments may be viable screening tools for identifying individuals at a high risk of falling to promote healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Physically active individuals may exhibit a decreased risk of falls and fractures because of their higher levels of physical fitness [ 11 , 12 ], and sedentary older adults with poor physical fitness must exert greater effort to execute activities necessary for independent living, which increases their risk of falling [ 13 ]. Therefore, physical fitness assessments may be viable screening tools for identifying individuals at a high risk of falling to promote healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, with increasing age and the transition to adolescence, the quantity and intensity of physical activity engaged in by individuals with IDs reduces further still [ 16 , 17 ]. To this end, participation in sport or physical activity can provide important health benefits at a physical, psychological, and social level, alongside equivalent improvements in quality of life, as has been stated by Luiselli [ 18 , 19 ]. Furthermore, scientific evidence exists that indicates that engagement in PA can improve levels of motivation, empathy, and social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Because physical activity and mental stress are factors that influence physical fitness. Cruzado et al (2017) in their study also showed differences in physical fitness between people who do physical activity and those who don't practice physical activity, where physical fitness performance is better in physically active people. Based on the results of the students fitness test, it appears that the efforts of Islamic boarding schools in maintaining the fitness of the students are still lacking.…”
Section: Resultsmentioning
confidence: 86%